SUPERNATURAL BELIEF IN JAVANESE CULTURE: INEVITABLE AND ERRONEOUS - Stuart A. Bruce (Celt: A Journal of Culture, English Language Teaching & Literature, 2003)
The Javanese people have a healthy beliefin ghosts. magic and the supernatural; one which often seems contradictory to the more scientifically-based beliefs held in the western world. These beliefs are born from ignorance and from culture. Ignorance here has a relationship to levels of both literacy and personal intelligence. and if ignorance causes a lack of understanding. lack of understanding is a breeding ground for belief in ghosts. The culture of the Javanese is the other major factor in producing such strong and widely-held beliefs. Traditional and modern popular cultures create a mental pre-conditioning that affects judgement. Similarly. collective belief and especially the use of story give the Javanese an excellent foundation for embraCing all things supernatural. Combined with prevalent social conditions. the Javanese are convinced. but wrongly so. of the existence of ghosts and magic.